2017
DOI: 10.1089/dia.2017.0007
|View full text |Cite
|
Sign up to set email alerts
|

“It Is Definitely a Game Changer”: A Qualitative Study of Experiences with In-home Overnight Closed-Loop Technology Among Adults with Type 1 Diabetes

Abstract: This study provides relevant insights for implementation of closed-loop in the real world. For people with diabetes who are less familiar with technology, remote monitoring for the first few days may provide reassurance, strengthen their trust/skills, and make closed-loop an acceptable option for more people with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Established guidelines recommend the use of CGM and its benefits in people with Type 1 diabetes have been demonstrated [2]. Furthermore, a small number of qualitative studies examining people's experiences with CGM are available [3][4][5][6][7][8][9][10][11]. A recent review of qualitative studies that explored the psychosocial impacts of CGM indicated that, in general, responses to the technology are positive [12].…”
Section: Introductionmentioning
confidence: 99%
“…Established guidelines recommend the use of CGM and its benefits in people with Type 1 diabetes have been demonstrated [2]. Furthermore, a small number of qualitative studies examining people's experiences with CGM are available [3][4][5][6][7][8][9][10][11]. A recent review of qualitative studies that explored the psychosocial impacts of CGM indicated that, in general, responses to the technology are positive [12].…”
Section: Introductionmentioning
confidence: 99%
“…Benefits include improved daytime [6] and night-time [6,7] glycaemic control, and psychosocial benefits of reduced worry [6] and burden [8,9], decreased fear of hypoglycaemia [9], decreased diabetes distress [8], improved sleep [6], increased treatment satisfaction [8], improved well-being [7], and trust in the system [5,8]. Concerns such as delays in responding to out of range numbers [8,9], algorithms that were too conservative [5], challenges around exercise [5][6][7][8]10], technical difficulties [6,8,10] such as inaccurate sensors or connectivity challenges [10], intrusive alarms [5,6,10] and concerns regarding the size of the devices [6][7][8], and the need to carry multiple devices [5,9] were all raised.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies have focused on the experiences of people with type 1 diabetes and/or their family members when using closed-loop systems. [3][4][5][6][7][8][9][10][11][12][13] Health professionals' perspectives have only received limited attention, including their views about the training, support, and resourcing needed to support individuals using the technology in routine clinical care. This is an important omission, given the evidence that a key mediating factor in people's access to and experience of using diabetes technologies is professionals being appropriately trained and supported.…”
Section: Introductionmentioning
confidence: 99%